Covid-19 epidemic in the dialysis units of the french speaking part of Belgium : special insight into patients on home dialysis - Fredéric Collart; Jean-Marin des Grottes; Thomas Baudoux; Charles Cuvelier; Frederic Debelle; Eric Goffin; Catherine Masset; Olivier Mat; Georges Cornet (RDPLF, 2020)
In the French-speaking part of Belgium, between march and end of may 2020, 284 patients have suffered a Covid-19 infection, 7,9% of the prevalent dialysis population. Some of them have been  diagnosed through rt-PCT as they were symptomatic, others, asymptomatic,  being diagnosed by swab viral culture. Fifty two patients died (18% of the positive patients). The vast majority of them were patients on hemodialysis, only ten cases have been observed in patients on home dialysis techniques. Primary renal disease were diabetes or renal hypertensive disease in more than 50% of the patients and the most important comorbidities were cardiac ischemic or congestive disease, autonomy problems, cancer and smoking habits.